2009
DOI: 10.1016/j.ijgo.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based maternal and perinatal healthcare practices in public hospitals in Argentina

Abstract: There is limited use of the selected evidence-based maternal and perinatal practices in public hospitals in Argentina and a large variation in their use among and within hospitals. Efforts should be made to increase the use of these evidence-based practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
(12 reference statements)
0
15
0
3
Order By: Relevance
“…As there was no follow-up of the newborns, it was not possible to detect improvement in indicators like neonatal mortality. However, it seems likely that improvements in care would lead to improvements in newborn health (33,34). Furthermore, the Hawthorne effect was a potential methodological limitation of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…As there was no follow-up of the newborns, it was not possible to detect improvement in indicators like neonatal mortality. However, it seems likely that improvements in care would lead to improvements in newborn health (33,34). Furthermore, the Hawthorne effect was a potential methodological limitation of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Kenyon et al [14] showed a reduction in maternal and neonatal morbidity, but not a statistically significant reduction in perinatal mortality, although a trend toward a beneficial effect was shown. In addition, a clear reduction in major markers of maternal and neonatal morbidity when antibiotics are administered makes a reduction in death possible [15]. …”
Section: Discussionmentioning
confidence: 99%
“…AMTSL to reduce postpartum hemorrhage was defined considering only the component prophylactic administration of 10 IU of oxytocin immediately after delivery of the neonate in a vaginal delivery to prevent hemorrhage (the other components of AMTSL are not recorded) [12,15]. …”
Section: Methodsmentioning
confidence: 99%
“…28 Nevertheless, Argentina's health system has struggled with adopting evidence-based, safe clinical practices. 29 Entrenched behaviours, such as the routine use of episiotomies or high rates of unjustified cesarean sections, which unnecessarily put women's bodies at risk, contribute to this failure. Argentina's legal response to these public health challenges involves imposing obligations on physicians to refrain from over-medicalized practices and requesting the Ministry of Health to issue health policies and practice protocols that identify and eliminate entrenched practices known to be harmful or unnecessary.…”
Section: Obstetric Violence As a Public Health Issuementioning
confidence: 99%